1. Identify the coefficients and constants of both equations.
Equation 1: -7x - 2y = -13
Equation 2: x - 2y = 11
2. Choose a variable to eliminate. In this case, the y variable is the easiest to eliminate.
3. Multiply both sides of Equation 1 by -1.
-1(-7x - 2y) = -1(-13)
7x + 2y = 13
Now we have:
Equation 1: 7x + 2y = 13
Equation 2: x - 2y = 11
4. Add Equation 2 to Equation 1.
(7x + 2y) + (x - 2y) = 13 + 11
8x = 24
5. Divide both sides of the resulting equation by 8 to solve for x.
8x/8 = 24/8
x = 3
6. Substitute the value of x back into one of the original equations to solve for y. Let's use Equation 2.
3 - 2y = 11
7. Rearrange the equation to solve for y.
-2y = 11 - 3
-2y = 8
8. Divide both sides of the equation by -2 to solve for y.
y = 8/-2
y = -4
Therefore, the solution to the system of equations is x = 3, y = -4.
what are the steps, in order, to solve the system of equations
-7x-2y=-13 x-2y=11
1 answer